An automatic frequency stabilized laser with hertz-level linewidth. (January 2022) - Guo, Xinqian; Zhang, Linbo; Liu, Jun; Chen, Long; Fan, Le; Xu, Guanjun; Liu, Tao; Dong, Ruifang; Zhang, Shougang
Highlights: Analog high-speed PID combined with digital automatic controller is developed. Automatic frequency stabilization of hertz-level linewidth laser system is realized. The continuous operation of an ultra-stable laser over a week is demonstrated. Abstract: The ultra-stable laser system has been widely used in a variety of fields. Recently, automatic laser frequency stabilization is crucial to some unmanned applications. This paper reports the development of the automatic laser frequency stabilization for the ultra-stable laser system with hertz-level linewidth. The hybrid automatic frequency stabilization circuits are combined with analog high-speed PID circuits and digital automatic controller. An external cavity diode laser is demonstrated to be frequency locked to a reference cavity with a control bandwidth over 2.1 MHz which can be improved. Beating with a second ultra-stable lasers, a median linewidth of 3.86 Hz is obtained via 203 repeated measurements. To characterize the reliability of automatic frequency stabilization, the laser is intendedly interrupted by 4432 times, while the laser frequency is relocked automatically. The mean time for the laser relocking is 4.86 s, and 90 % of the experiments can be relocked within 6 s. Moreover, one week of laser frequency stabilization with automatic relocking is demonstrated. The design of the auto-locking laser system can be applied for field and space applications.